A Proposal for Automatic Testing of GUIs Based on Annotated Use Cases. (5th October 2009) - Mateo Navarro, Pedro Luis; Sevilla Ruiz, Diego; Martínez Pérez, Gregorio
Abstract : This paper presents a new approach to automatically generate GUI test cases and validation points from a set of annotated use cases. This technique helps to reduce the effort required in GUI modeling and test coverage analysis during the software testing process. The test case generation process described in this paper is initially guided by use cases describing the GUI behavior, recorded as a set of interactions with the GUI elements (e.g., widgets being clicked, data input, etc.). These use cases (modeled as a set of initial test cases) are annotated by the tester to indicate interesting variations in widget values (ranges, valid or invalid values) and validation rules with expected results. Once the use cases are annotated, this approach uses the new defined values and validation rules to automatically generate new test cases and validation points, easily expanding the test coverage. Also, the process allows narrowing the GUI model testing to precisely identify the set of GUI elements, interactions, and values the tester is interested in.